Pyrolysis of rice straw for bioenergy: Kinetics, reaction mechanism, and by-products using TG and Py-GC/MS analysis - Shaopeng WANG; Yadi HU; Yufei WANG (Journal of Thermal Science and Technology, 2025)
In this study, the pyrolysis kinetics and mechanism of rice straw were investigated using thermogravimetric analysis (TGA) and pyrolysis gas chromatography-mass spectrometry (Py-GC/MS). The activation energy and thermodynamic parameters including the pre-exponential factor, Gibbs free energy, enthalpy, and entropy were calculated by the Kissinger-Akahira-Sunose (KAS) and Friedman (FR) methods. The Criado method was further used to determine the kinetic model of rice straw during the pyrolysis process. The Py-GC/MS results showed that the main components in the rice straw pyrolysis products were carbon dioxide, carbonyl compounds, phenolic compounds, aliphatic compounds, aromatic hydrocarbons, and heterocyclic compounds. The mean values of Ea obtained by the KAS and FR methods were 181.6 and 182.1 kJ/mol, respectively. When α was less than 0.45, the three-dimensional diffusion (D3) model fit well with the thermal degradation of rice straw, while for α>0.45, it transformed into a random nucleation (F3) model. The value of enthalpy change indicated that the formation of the activated complex required an additional 5 kJ/mol of energy; beyond the activation energy, the mean value of entropy during the thermal degradation process was about 10.53 J·mol−1·K−1, indicating that the system was more closely balanced with thermodynamics and that the thermal degradation process was relatively easy to carry out. Therefore, the findings of this study highlight the favorable conditions for the energy utilization of rice straw biomass.